The Skills Road : Skills for Employability in Uzbekistan - Ajwad, Mohamed Ihsan (World Bank, Washington, DC, 2014)
This report addresses a fundamental question facing policymakers in Uzbekistan: are worker skills hindering employment outcomes? The main finding of the report is that, indeed, worker skills gaps are hindering employment outcomes in Uzbekistan. In fact, employers—particularly formal sector employers—seek workers who possess both cognitive and non-cognitive skills. The higher employability and higher wage rates among higher skilled workers is mostly explained by the use of those skills in workplaces. But, skills gaps persist, leading a large share of employers to report shortages of high-skilled workers. These shortages are resulting in high wage premiums—tertiary graduates earn on average 55 percent more than similar workers with a general secondary education. However, large variations in observed skills among adults with the same level of educational attainment indicate that formal education is failing too many people. The report outlines weaknesses in the way skills are formed in Uzbekistan. While skills are developed during different stages in the life cycle and a host of actors are involved—families, for example, play a central role—the education and training system has a mixed record in skill formation. The report argues that the government could do more to align the skills imparted through the education and training system with the needs of employers. The government can also do more to get children off to the right start by investing in early childhood development, where rates of return to investment are generally very high and important soft skills are learned. Finally, more can be done to match the supply of skills with employer demand by improving the use of information in matching skills to jobs in the labor market.